Alterations in the Baroreceptor Reflex in Conscious Dogs with Heart Failure - Higgins, Charles B. (1972)
The effectiveness of the baroreceptor reflex in conscious dogs with experimental cardiac hypertrophy and heart failure was compared with that in a group of normal conscious dogs. Cardiac hypertrophy and heart failure were produced by tricuspid avulsion and progressive pulmonary stenosis. The sensitivity of the baroreceptor reflex to transient hypertension was assessed by determining the slope of the regression line relating the prolongation of the R-R interval to the rise in systolic arterial pressure during the transient elevation of arterial pressure induced by an intravenous injection of 1-phenylephrine. The mean slope averaged 22.4±2.3 msec/nm Hg in 16 normal animals. 23.1 ±1.5 in five sham-operated animals, and was significantly reduced to 8.3 ±0.8 in 10 dogs with hypertrophy alone (P < 0.001), and to 3.3±0.5 in nine dogs with heart failure (P < 0.001). The response to baroreceptor hypotension was compared during bilateral carotid artery occlusion (BCO) in six normal and six heart failure dogs previously instrumented with Doppler flow transducers on the superior mesenteric and renal arteries. During BCO, in normal dogs arterial pressure increased 52±4 mm Hg, heart rate 33±2 beats/min, mesenteric resistance 0.17±0.03 mm Hg/ml per min, and renal resistance 0.37±0.10 mm Hg/ml per min. In the heart failure group all of these variables increased significantly less (P < 0.01); arterial pressure rose 25 ±3 mm Hg, heart rate 13 ±4 beats/min, mesenteric resistance 0.04±0.007 mm Hg/ml per min, and renal resistance 0.18±0.09 mm Hg/ml per min. Thus, in heart failure, all measured systemic and regional circulatory adjustments consequent to baroreceptor hypo- and hypertension are markedly attenuated. This study demonstrates a profound derangement of a major cardiovascular control mechanism in experimental heart failure.